1997
DOI: 10.1046/j.1365-2648.1997.1997025915.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of communications in nursing care for elderly people: a review of the literature

Abstract: Communication in nursing care is an important topic assessing the specific needs of elderly patients and providing nursing care that is tailored to the individual patient's needs. In this review of the literature, we describe the role attributed to communication in theoretical nursing models and we report how research in communication in nursing elderly patients has taken place over the last ten years. It appears that since the eighties there has been an increase in observation studies into nurse-patient commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
1
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 43 publications
5
89
1
2
Order By: Relevance
“…These ®ndings were not attributable to the differences between patient populations in the two care settings, such as age, gender, perceived health or length of time the nurse has cared for the patient. An earlier study (Caris-Verhallen et al 1997b) showed that those patient characteristics were hardly related to the way nurses communicate with their patients. The more frequent occurrence of non-verbal behaviour may re¯ect the familiar atmosphere in the home for the elderly.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…These ®ndings were not attributable to the differences between patient populations in the two care settings, such as age, gender, perceived health or length of time the nurse has cared for the patient. An earlier study (Caris-Verhallen et al 1997b) showed that those patient characteristics were hardly related to the way nurses communicate with their patients. The more frequent occurrence of non-verbal behaviour may re¯ect the familiar atmosphere in the home for the elderly.…”
Section: Discussionmentioning
confidence: 97%
“…These types of study are not possible in nursing practice, but restricted to experimental arrangements. In analysing verbal behaviour and the atmosphere during the encounter, nurses rarely showed hostility or disagreement with their patients (Caris-Verhallen et al 1997b). Therefore patient-directed gaze, smiling, head nodding, forward leaning and affective touch were considered as positive.…”
Section: Methodological Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thereby, the use of nonverbal communication, in addition to verbal communication, is essential with people who have limited verbal comprehension [7]. Nonverbal behaviour is an eminent mode of expressing empathy and support and an important tool to make contact with residents [8][9][10].…”
Section: Introductionmentioning
confidence: 99%